1995
DOI: 10.1016/0092-8674(95)90539-1
|View full text |Cite
|
Sign up to set email alerts
|

The drosophila schnurri gene acts in the Dpp/TGFβ signaling pathway and encodes a transcription factor homologous to the human MBP family

Abstract: Decapentaplegic (dpp), a TGF beta-related ligand, plays a key role in Drosophila development. Although dpp receptors have been isolated, the downstream components of the signaling pathway remain to be identified. We have cloned the schnurri (shn) gene and show that it encodes a putative zinc finger transcription factor homologous to the human major histocompatibility complex-binding proteins 1 and 2. Mutations in shn affect multiple events that require dpp signaling as well as the transcription of dpp-responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
1
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(115 citation statements)
references
References 41 publications
3
106
1
5
Order By: Relevance
“…3A, bottom ;Campbell and Tomlinson, 1999;Jaźwiń ska et al, 1999a,b;Minami et al, 1999). A critical transcription factor mediating this DPP-dependent repression of brinker is the zinc finger DNA-binding protein Schnurri (Shn; German for whiskers; Arora et al, 1995;Grieder et al, 1995;Staehling-Hampton et al, 1995). shn encodes a large protein (ϳ275 kDa) composed of eight zinc fingers (arranged in four clusters), which interacts with Smads (Mad and Medea, orthologs of vertebrate Smads 1/5/8 and 4, respectively) to mediate DPP signaling (Dai et al, 2000;Udagawa et al, 2000).…”
Section: Schnurri a Transcriptional Partner With Multiple Personalitiesmentioning
confidence: 99%
“…3A, bottom ;Campbell and Tomlinson, 1999;Jaźwiń ska et al, 1999a,b;Minami et al, 1999). A critical transcription factor mediating this DPP-dependent repression of brinker is the zinc finger DNA-binding protein Schnurri (Shn; German for whiskers; Arora et al, 1995;Grieder et al, 1995;Staehling-Hampton et al, 1995). shn encodes a large protein (ϳ275 kDa) composed of eight zinc fingers (arranged in four clusters), which interacts with Smads (Mad and Medea, orthologs of vertebrate Smads 1/5/8 and 4, respectively) to mediate DPP signaling (Dai et al, 2000;Udagawa et al, 2000).…”
Section: Schnurri a Transcriptional Partner With Multiple Personalitiesmentioning
confidence: 99%
“…Originally described in Drosophila (Arora et al 1995;Grieder et al 1995;Staehling-Hampton et al 1995), Schnurri binding to the SMAD1/5-SMAD4-binding sites GRCGNC-N 5 -GTCT described above is thought explain the requirement for the N 5 spacing (Fig. 1B) (Pyrowolakis et al 2004).…”
Section: Transcription Factors Interacting With Smad1/5mentioning
confidence: 99%
“…Both Spalt (Lecuit et al 1996;Nellen et al 1996) and the PRDII-BF1 family member Schnurri (Arora et al 1995;Grieder et al 1995) have been shown to be targets of signaling by the TGF-f3-1ike protein Decapentaplegic. The sequence similarities among SEM-4, Spalt, and PRDII-BF1 family members raise the possibility that SEM-4 activity might also be controlled by a signal transduction pathway.…”
Section: V5paapp Cell Death Pnp Hypodermal Cellsmentioning
confidence: 99%
“…This family includes the human proteins MBP-2 (van't Veer et al 1992) and KBP-1 (van't Veer et al 1992), as well as the Drosophila protein Schnurri (Arora et al 1995;Grieder et al 1995), which acts in the signaling pathway mediated by the transformation growth factor-~ (TGFq3)-related growth factor Decapentaplegic. The zinc fingers in SEM-4 and Spah are more similar to each other than to the zinc fingers in PRDII-BF1, MBP-2, KBP-1, or Schnurri, indicating that SEM-4 and Spah are more closely related to each other than to the other proteins.…”
Section: The Sem-4 Protein Contains Pairs Of Zinc Fingers That Are Simentioning
confidence: 99%